UPAYA KONSERVASI HUTAN MANGROVE DI DESA PEMATANG KUALA KECAMATAN TELUK MENGKUDU KABUPATEN SERDANG BEDAGAI - Tania, Wulan Dira; Harefa, Meilinda Suriani (Jurnal Samudra Geografi, 2025)
Mangrove Forest Conservation Efforts in Pematang Kuala Village, Teluk Mengkudu District, Serdang Bedagai Regency. This study aims to determine what factors cause mangrove forest damage and what conservation efforts have been carried out in the mangrove forest area. The location of the study is the mangrove forest ecosystem in Pematang Kuala Village with a land area of ​​52 ha. The results of the study showed that: (1) In this mangrove forest area there are several types of mangroves that are cultivated, namely, Rhizophora, Avichennia, Brugueira and also Nipah. If examined, the factors or problems of mangrove forest damage in this village are due to natural factors themselves. (2) Rehabilitation efforts are carried out using the 1x1 planting technique or using the spacing clump planting technique. Using the spacing clump technique can reduce the high level of damage or death in the mangrove planting process. There are several forms of conservation efforts, including rehabilitation, preservation, maintenance, utilization and also preservation.